When the Levees Break : Re-visioning Regulation of the Securities Markets. - Kunz, Karen (Lexington Books, 2016)
This book examines the expanding reach of the securities market in the US financial system. It analyzes key elements such as the rise of technology, the role of hedge funds, and the bloated agency system, and argues that the current structure is doomed to fail. It suggests a new structure capable of withstanding the challenges of modern markets.